A rapid and simple single-stage method for Ca separation from geological and biological samples for isotopic analysis by MC-ICP-MS. Issue 3 (6th February 2018) - Lanping, Feng; Zhou, Lian; Yang, Lu; Zhang, Wen; Wang, Qian; Shuoyun, Tong; Hu, Zhaochu
Abstract : A simple and rapid single-step Ca separation method implemented by using a combination of a DGA column and vacuum box. Abstract : A new simple and rapid method was developed for the purification of Ca from geological and biological samples. The proposed separation protocol is based on DGA resin and consists of only three elution steps and two types of eluents (6.8 mL 4 mol L −1 HNO3 and 3 mL DI-water), which afford a straightforward separation of Ca with a high yield (95–99%), good purity and low blank level. Moreover, a vacuum box was employed which enables Ca purification for a batch of twelve samples within two hours, with greatly improved efficiency compared to conventional gravity flow separation methods. Ca isotopic ratios were measured by multi-collector inductively coupled plasma mass-spectrometry (MC-ICP-MS) using a standard–sample bracketing method. Based on repeated measurements of NIST SRM 915a and Alfa Ca, the long-term reproducibility was evaluated at ±0.07‰ (2SD) for δ 44/42 Ca. The validity of the proposed method was demonstrated by the analysis of thirteen international geological and biological reference materials with satisfactory results which are in good agreement with published values. Therefore, the proposed method can be used for a rapid and efficient determination of stable Ca isotopic ratios in geological and biological samples.